Dynamic focusing of an ultrasonic be am by means of a phased annular array using a pulse technique - KUJAWSKA, Tamara (Archives of Acoustics, 1983)
An approach to compute, the transient radiation resulting from an impulse velocity motion of an array of annular pistons in a rigid planar infinite baffle is presented. The approach is limed on developing the expression for an impulse response function, which is the time-dependent velocity potential at a spatial point resulting from an impulse velocity of a piston. The time-dependent pressure for any piston velocity motion may then be computed by a convolution of the piston velocity with the appropriate impulse response.Numerical results of near field time-dependent radiation from annular phased array are discussed for pulsed velocity conditions. The lateral acoustical pressure distribution at different field depths is shown. The ultrasonic beam-width as a function of the depth for every focal zone is also presented. Obtained results were compared with corresponding dependences for steady states.